Tamarind shell extract mitigates D-glucose-induced eye malformations: Restorative actions on key developmental markers in chick embryos and ARPE-19 cells - Xi-you Li; Xiao-yuan Gu; Bai-ling Zhou; Bun Tsoi; Wei-xi Li (Journal of Functional Foods, 2024)
Eye deformity, a noteworthy embryopathy, is intricately linked with maternal diabetes, frequently resulting in embryonic malformation or even death. In this investigation, a hyperglycemic chick embryo model was established to delve into the protective potential of tamarind shell extract (TSE) on eye development. Chick embryos were administered with TSE (at dosages of 1, 2, and 4 µg/egg) through air sac injection on embryo development day 0 (EDD0) and later exposed to D-glucose (0.4 mmol/egg) on EDD1. To validate our findings, we replicated hyperglycemic environment using D-glucose in ARPE-19 cell model. Our research unveiled that TSE proficiently counters O-GlcNAcylation of proteins in the presence of D-glucose, thereby reinstating levels of key proteins involved in eye development, including Pax6, Daam1, mTOR, and Cdc42. Furthermore, TSE was pinpointed to curtail the D-glucose concentration within the embryo eye, considerably decreasing the accumulation of reactive oxygen species and malondialdehyde accumulation in both the ARPE-19 cells and chick embryos. Beyond its fundamental role in boosting the cellular antioxidative activity, the improved expression of apoptosis-related proteins like Caspase-3, BAX, BCL-2 and other like PI3K and AKT were observed. This suggests a probable activation of the PI3K-AKT-mTOR pathway on ARPE-19 cells by TSE, thereby downregulating apoptotic proteins in ARPE-19 cells during oxidative stress. TSE may become a potent natural countermeasure against D-glucose-induced eye malformation.